Hubungan Disposisi Matematis dengan Kemampuan Pembuktian Matematika: Correlation of Mathematical Dispositions and Mathematical Proof - Ni Ketut Erawati (FPMIPA IKIP PGRI Bali, 2019)
This study aims to describe the relationship between mathematical disposition and the mathematical proof of students, especially in real analysis subjects. This research was conducted at IKIP PGRI Bali in 2018 with 25 students in semester Va. The instrument of data collection is a test of mathematical proof which is one of the achievements in learning real analysis and mathematical disposition questionnaire. Data was analyzed with the Spearman rank correlation. The results of the analysis show that the contribution of mathematical disposition to the student's evidence ability is 18.4%, but based on the statistical test the relationship is not significant. The results of this study indicate that the ability to prove the mathematics of students does not depend on the mathematical dispositions they have but rather the mastery of the material being studied. Therefore understanding the concepts and doing mathematical proof exercise is the most important thing